Narrating Islamism in Indonesia: State, Agency, and Social Resilience - Maufur, Maufur (Program Studi Studi Agama-Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2017)
Islamism or the so-called political Islam is conceptualized as a socio-political, rather than a solely religious phenomenon. Inherently characterized by a singularly defined religious concept of purity and a clear-cut distinction between “we” and “them”, it manifests into a various form of activities where “terrorism” is the most violent one. Following a series of terrorist attacks in the country, the Indonesian government through The National Counter-Terrorism Agency (BNPT) launched a de-radicalization program that aims to restrain and combat religious radicalism and “terrorism”, particularly through its “stick and carrot” approach. Despite its success story in pacifying some terrorist activities in the country, the program is severely criticized for not dealing with the root causes of terrorism. It is also considered counter-productive as it creates resistance and hatred toward the state for specifically targeting Islam and, therefore, it provides incentives for religious radicalism and terrorism. The research conducted in Yogyakarta Province found that Islamism spreads and gains acceptance in the certain sections in public through certain social channels and agencies. However, this paper argues that the existing cultural virtues and local wisdom could create social resilience against such radicalization process.   Keywords:  Islamism, Radicalism, Terrorism, Local Wisdom